The Impact of Structural Changes on Sound Pressure Levels in a Neonatal Intensive Care Unit - CARVALHAIS, Carlos; RODRIGUES, Célia; XAVIER, Ana; SILVA, Manuela V.; SANTOS, Joana (Archives of Acoustics, 2021)
The design of neonatal intensive care units (NICU) influences both patient safety and clinical outcomes as well as the acoustic conditions. In NICU exposure to sound pressure levels above the recommended can affect both neonates and healthcare staff. This study aimed to evaluate the sound pressure levels and to assess noise perception of professionals in a NICU before and after structural modifications and layout redesign. The measurements were performed with a sound level meter. A questionnaire was given to staff before and after the intervention. The opinion of healthcare staff regarding noise in NICU was better after the intervention, when compared with the responses previously given. The results showed that noise levels were excessive in the NICU (before and after), exceeding the international recommendations, with the levels ranging between 46.6 dBA to 57.8 dBA before and 52.0 dBA to 54.0 dBA after intervention. Overall, there is a need for more research in order to verify the effectiveness of some actions and strategies to reduce the impact of noise in NICU.